2021
DOI: 10.3390/microorganisms9050914
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Phosphate Solubilizing Streptomyces sp. Endemic from Sugar Beet Fields of the Beni-Mellal Region in Morocco

Abstract: In the course of our research, aimed at improving sugar beets phosphorus nutrition, we isolated and characterized Streptomyces sp. strains, endemic from sugar beet fields of the Beni-Mellal region, which are able to use natural rock phosphate (RP) and tricalcium phosphate (TCP) as sole phosphate sources. Ten Streptomyces sp. isolates yielded a comparable biomass in the presence of these two insoluble phosphate sources, indicating that they were able to extract similar amount of phosphorus (P) from the latter f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In our previous research [ 40 ], we successfully isolated 10 Streptomyces spp. and revealed their phosphate solubilization capacities and siderophore production.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous research [ 40 ], we successfully isolated 10 Streptomyces spp. and revealed their phosphate solubilization capacities and siderophore production.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that the solubilization process might involve the excretion of organic acids. Interestingly, AI yielded much better biomass ( Figure 3 ) and was shown to excrete siderophores, but not the CYM strain [ 40 ], whereas BYC released a rather small amount (2-fold less, 61 mg/L). However, this strain produced siderophores and was selected as the best phosphate-solubilizing strain from both RP and TCP [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations